2013
DOI: 10.1016/j.virol.2013.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the telomere integrated genome of human herpesvirus 6A and 6B

Abstract: Human Herpesvirus 6B (HHV-6B) is the causative agent of roseola infantum. HHV-6A and 6B can reactivate in immunosuppressed individuals and are linked with severe inflammatory response, organ rejection and central nervous system diseases. About 0.85% of the US and UK population carries an integrated HHV-6 genome in all nucleated cells through germline transmission. We have previously reported that the HHV-6A genome integrated in telomeres of patients suffering from neurological dysfunction and also in telomeres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
59
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 42 publications
5
59
0
5
Order By: Relevance
“…Analysis of the integrated virus genome revealed that the perfect TMR of the DR R region are fused to the host chromosome accompanied by a loss of the pac2 sequence, consistent with an integration mediated by HR between the viral TMR and the host telomere (5). At the other end of the viral genome, the pac1 region is also lost and additional telomeric repeats are added, suggesting that the TMR in DR L is a substrate for the generation of a new telomere (29)(30)(31).…”
mentioning
confidence: 78%
“…Analysis of the integrated virus genome revealed that the perfect TMR of the DR R region are fused to the host chromosome accompanied by a loss of the pac2 sequence, consistent with an integration mediated by HR between the viral TMR and the host telomere (5). At the other end of the viral genome, the pac1 region is also lost and additional telomeric repeats are added, suggesting that the TMR in DR L is a substrate for the generation of a new telomere (29)(30)(31).…”
mentioning
confidence: 78%
“…These repeated sequences likely play a major role in the process of chromosomal integration of the HHV-6 genome (ciHHV-6) (see below). This integration has been reported to occur through a junction between host chromosomes and the perfect telomeric repeats at the right end of DR R (23)(24)(25). The overall number of protein-encoding open reading frames (ORFs) is about 110 to 120 according to the different published nucleotide sequences (26)(27)(28).…”
Section: Genome and Genetic Variabilitymentioning
confidence: 99%
“…All three human roseoloviruses contain mammalian telomeric sequences at their genomic termini, and telomeres are the site of integration of HHV-6A and HHV-6B in patients with chromosomally integrated HHV-6 [36,37]. Telomeric integration occurs in infected cultured Jjhan and HEK-293 cells, establishing a system for mapping and characterizing the mechanistic processes of integration.…”
Section: Latency and Reactivationmentioning
confidence: 99%
“…If integration is a mechanism of latency, a functional virus genome must be excised from telomeres in order to reactivate full lytic infection. HEK293 cells with integrated HHV-6A can produce viral genome concatamers upon treatment with the histone deacetylase inhibitor trichostatin A [36]. Huang et al [43] noted that the telomeres attached to integrated HHV-6 genomes are frequently shortened and associated with detection of circular viral genomes.…”
Section: Latency and Reactivationmentioning
confidence: 99%